2018
DOI: 10.3389/fimmu.2018.01113
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Serological Biomarkers in Rheumatoid Arthritis and Their Combination to Improve Diagnostic Performance

Abstract: IntroductionThe diagnosis of rheumatoid arthritis (RA) is based on a combined approach that includes serological markers such as rheumatoid factor (RF) and anti-citrullinated peptide/protein antibodies (ACPA). The goal of this study was to evaluate the clinical performance of several RF and ACPA immunoassays for the diagnosis of RA, as well as the diagnostic value of a combinatory approach with these markers.MethodsThe study cohort included 1,655 patients from the Swiss Clinical Quality Management registry wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 48 publications
1
13
1
Order By: Relevance
“…Our data confirm previous reports where ACPA positivity was detected in about 1% to 13% of PsA and axSpA patients, depending if second or third generation anti-cyclic citrullination peptide antibody assay were used (35). This alone does not rule out the involvement of a humoral immune response, as it should be appreciated that back in the 1990s, a number of studies demonstrated reactivity to fibrocartilage proteins, including aggrecan, suggesting that an autoimmune antibody response may underlie enthesitis and spondylitis pathology (36).…”
Section: Discussionsupporting
confidence: 92%
“…Our data confirm previous reports where ACPA positivity was detected in about 1% to 13% of PsA and axSpA patients, depending if second or third generation anti-cyclic citrullination peptide antibody assay were used (35). This alone does not rule out the involvement of a humoral immune response, as it should be appreciated that back in the 1990s, a number of studies demonstrated reactivity to fibrocartilage proteins, including aggrecan, suggesting that an autoimmune antibody response may underlie enthesitis and spondylitis pathology (36).…”
Section: Discussionsupporting
confidence: 92%
“…In previous studies, the agreement between the 2 tests has been evaluated almost exclusively in patients with RA, with conflicting results. In fact, some studies demonstrated good agreement between anti‐CCP2 and anti‐CCP3 antibodies (23,24,35–38), whereas other studies showed a significant discrepancy between the 2 tests (39,40). The lack of agreement was attributed to several factors, such as borderline results, interassay discrepancy, the fact that anti‐CCP3 assays may include additional epitopes not present in the anti‐CCP2 antigen sequence, and intertest variability depending on other components of the kits (i.e., standards, secondary antibody, or the cutoff used).…”
Section: Discussionmentioning
confidence: 99%
“…In 2 studies (22,23), anti‐CCP3 was found to discriminate better than anti‐CCP2 between RA and non‐RA in patients negative for rheumatoid factor (RF). Interestingly, the combination of these 2 assays was shown to have higher specificity for the identification of RA patients than the individual assays (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…Considered useful in early stages of the disease to predict the development of erosions and the presence of the IgA isotype is associated with extra-articular manifestations. Aggressive development of the disease and decreased response to anti-TNF therapy have been reported at high levels [ 42 , 53 , 57 , 68 , 74 , 75 , 99 , 109 , 121 , 124 ] PHASE 1 Anti-citrullinated protein antibodies (ACPA) Non-omics Biomarker more sensitive (60–80%) and specific (95–98%) for the diagnosis of RA than RF. ACPA + patients develop a more aggressive and erosive progressive disease clinical phase compared to ACPA- patients; Positivity has been associated with a better response to treatment in early stages but medication-free remission is less frequent.…”
Section: Resultsmentioning
confidence: 99%
“…Baseline levels can be predictive for the response to methotrexate and ACPA + subjects are associated with a better response to abatacept independent of disease activity. It has been detected in healthy patients therefore increases the risk of developing RA by 5% in the next 5 years [ 42 , 51 , 53 – 57 , 65 , 68 , 74 , 75 , 99 , 109 , 110 , 112 , 121 ] PHASE 1 Anticarbamylated protein (anti-CarP) antibodies Non-omics Association with rapid radiological damage and severe course of the disease independent of the ACPA value. In patients ACPA—it is associated with the development of arthralgias [ 57 , 65 , 74 , 109 , 112 ] PHASE 1 Regulatory B lymphocytes (Breg) Non-omics Protective role in RF + patients (Lower T2/Breg levels) [ 62 ] PHASE 1 Erythrocyte Sedimentation Rate (ESR) Non-omics Nonspecific indicator of the amount of inflammation in the elevated body in patients with RA.…”
Section: Resultsmentioning
confidence: 99%